Interactive ball for enhancing communication for autism child / Norazlin Mohamad … [et al.] - Mohamad, Norazlin; Che Mood, Aslinda; Andenan, Nurnajwa Inani; Noor Esa, Ahmad Muiz (Division of Research and Industry Linkages, 2017)
The Autism Society of America (2000) defines autism as "a complex developmental disability that typically appears during the first three years of life and is the result of a neurological disorder that affects the normal functioning of the brain, impacting development in the areas of social interaction and communication skills. Both children and adults with autism typically show difficulties in verbal and non-verbal communication, social interactions, and leisure or play activities. “The children with autism commonly will have delay development in communication and social interactions. They tend to have delay in speech and language and show their expression using their own way. Thus, the social interaction between the children and carer will be limited and misunderstanding. Their focus may be distracted due to other things that may catch their curiosity in short time. To develop better communication skill, the children need to have interaction between their friends or carer. Training procedures in discrimination skills included choice making, making desired, preference assessment, differential reinforcement, and match to sample discrimination (Simer & Cuvo, 2009). The target of population of this product is between 3 to 7 years old. Product are using ball with interactive features in order to develop interest in the children. Thus, modification of the change detection task can be applied on interactive ball that is made for young autism children need to match their stages of development and emerging abilities. Our product is using interactive way to promotes children awareness towards communication in life using daily activities. Typically, it is safe and appropriate play materials to keep, to hold, to reach, and to look at an attractive the pictures placed surround the ball so children can see them. The children can understand the description of the pictures and be able to interpret the action based on the desired of what they want and do not want to do (such as they want to play, to eat and go to the toilet), the instructions (such as go to bed, do not argue and clean up the toys), the expressions (such as happy, sad and anxious) and the picture of task (spelling, arranging and do physical activities).With the ball, autism children can use it to inform the carer or others about their desire, their interest and their hate. Visual discrimination skills deficit among autism children can be improve in their communication skills Speech and language development supports child's ability to communicate, and express and understand feelings. It also supports thinking and problem-solving, and developing and maintaining relationships. In addition, ‘physical therapies' or career will overcome this problem, it is important to help in their communication skills on speech and language. It is expected that this modified task can encourage autism children to practically use the interactive ball to express their desired and need, and healthy is only one step away and a little encouragement is needed to help 'silent' autism children to become more active.